Salvador Benesdra’s View of Neoliberalism in El traductor [The Translator] - Guzmán Rubio, Federico (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The study of El traductor [The Translator] focuses the relationship between Latin American neoliberalism and literature. Nevertheless, neoliberalism as the main economic and political hegemonic system in the region since 1940’s, it has not been studied in connection with literature. In this paper, the History of neoliberalism reforms are considered where it has been criticized their ideological support. At the same time, it is exposed the patterns presented in Benesdra work related to Latin American neoliberalism. The result is an approach of how the author represented the power of neoliberalism in different scopes like social frameworks, labour sphere, emotional scenarios, and political and cultural contexts. Additionally, it is outlining Brenesda’s critical view of neoliberalism.